Future of digital health and precision medicine in rheumatology practice in India - Joydeep Samanta; Debashish Mishra (Indian Journal of Rheumatology, 2022)
With the digitalization of the services across various sectors in an Indian setting, health care is also influenced by the same. It was evidenced during the COVID-19 pandemic that Indian patients were orienting themselves toward more teleconsultations and digital and smartphone-based health care. This not only saves time and money but also reduces the chances of hospital-acquired cross infections. This is more important for patients with rheumatic diseases who try to avoid frequent hospital visits despite the need for regular health-care consultations due to the aforementioned reasons. Apart from the telemedicine and smartphone apps, health care is expanding to robotics and artificial intelligence-based machine learning. Healthcare digitalization will lead to the expansion of precision based medicine. When more robust genomics, proteomics, metabolomics, and transcriptomics data become available for Indian patients with rheumatic diseases, management then would be more personalized than blanket therapy. However, such futuristic advancements face challenges of their own which are neither time nor knowledge bound. We are currently just at the tip of this massive iceberg. We describe various aspects of the future of digital health and precision medicine in rheumatology in an Indian setting.